Acute Campylobacter spp. gastroenteritis in the Pediatric Emergency Department of a level II hospital - Sá, Liliana (2022)
Introduction: Campylobacter spp. is the main cause of pediatric acute bacterial gastroenteritis (ABG) in the European Union, with greater incidence in children under five years old. Most patients present complete recovery within days of infection, with no associated comorbidities. Antibiotic therapy should be reserved for severe cases. Objectives: The aim of this study was to investigate the epidemiology, symptoms, treatment, and complications of Campylobacter spp. infection in pediatric patients with ABG. Material and methods: Case-by-case review of the clinical records of patients evaluated in the Pediatric Emergency Department of a level II hospital with a diagnosis of ABG and Campylobacter spp. isolated from stool samples over a five-year period (2013-2017). Results: Of the 1990 stool tests performed, 637 (32%) were positive for the presence of bacteria. Campylobacter spp. was identified in the samples of 459 patients (72%). Eighteen patients were excluded for insufficient data, making up a final sample of 441 patients, with a mean age of three years old. Clinically, patients presented with aqueous diarrhea (59.6%), bloody diarrhea (43.8%), bloody and mucus diarrhea (15.4%), mucus diarrhea (3.9%), vomiting (36.3%), abdominal pain (24.3%), fever (63%), seizures (0.9%), and rash (0.2%). Eighty-nine patients were hospitalized. Eleven patients received antibiotic therapy. Discussion: This study represents the largest national case-by-case review of ABG by Campylobacter spp. in the pediatric population. Campylobacter was the main bacteria identified, mostly associated with self-limited disease. Conclusion: A judicious use of stool tests allows etiological identification in ABG. The growing number of cases of ABG by Campylobacter spp. reinforces the need for better hygiene procedures.